The dynamics of collective memory in the Ukraine crisis: a transitional justice perspective - Nuzov, Ilya (International journal of transitional justice, 2017)
This article addresses the role of collective memory in the post-Soviet transitions of Ukraine and Russia, and its relationship with identity building and bilateral foreign policy before and after Ukraine’s 2014 Maidan revolution. Based on an empirical evaluation of the respective states’ memorialization practices, I argue that the politics of memory in Russia facilitated the annexation of Crimea and the armed conflict in Donbass, and that Ukraine’s ontological and physical security crisis precipitated the 2015 decommunization laws addressing its Soviet past. I draw preliminary conclusions as to whether these memory laws could advance the larger transitional justice (TJ) objectives of reconciliation and democratization in Ukraine in the prevailing regional political context. Analysis of the historical narratives attendant to the Ukraine crisis shows that instead of advancing TJ, current legislation is likely to fuel the ideological divide between Ukrainians and between Ukraine and Russia, exacerbating these divisions. The article concludes by considering a truth commission to advance domestic and regional reconciliation.